Good Enough for An Affair. Self–Enhancement of Attractiveness, Interest in Potential Mates and Popularity as A Mate. Issue 1 (January 2016) - Schröder–Abé, Michela; Rentzsch, Katrin; Asendorpf, Jens B.; Penke, Lars
Using data from the Berlin Speed Dating Study, we tested rival hypotheses concerning the effects of self–enhancement of attractiveness on dating outcomes. Three hundred eighty–two participants took part in one of the 17 speed–dating sessions. After each speed–dating interaction, participants indicated how interesting they found the respective person as a long–term and short–term partner. Using social relations analyses, we computed perceiver effects (being more or less choosy) and target effects (being rated as more or less interesting) of long–term and short–term partner ratings. Self–enhancement was operationalized as the discrepancy between self–rated attractiveness and four components of actual attractiveness (observer–rated facial and vocal attractiveness, height and body mass index). Results indicated that self–enhancers were less choosy with respect to their interest for short–term partners, which was especially true for men, but more choosy with respect to long–term partners. With regard to popularity as a mate, potential partners indicated that they found self–enhancers more interesting as short–term partners but not as long–term partners. As self–enhancement is a key component of narcissism, these results are consistent with findings that narcissists perceive many sexual affairs as an achievement, while preferring selected 'trophy' long–term partners, and narcissists have a charming appeal for short–term, but not lasting, social relationships. Copyright © 2015 European Association of Personality Psychology